CICERO, PRO MURENA 47 AND 85. (16th April 2014) - Dyck, Andrew R.
<x content-type="archive" xml:space="preserve">Abstract</x> Cicero is narrating various proposals advanced by Servius Sulpicius Rufus in an attempt to save his failing consular campaign of 63. In addition to the lex Tullia de ambitu discussed in the preceding section, he mentions this proposal that was blocked in the senate. The text printed is that of Clark, who compares [Sall.] 2.8.1, citing a law promulgated by C. Gracchus in his tribunate: ut ex confusis quinque classibus sorte centuriae vocarentur. On this basis Clark suspected that the transmitted praerogationum conceals a reference to the praerogativa (centuria), the first to vote in the comitia centuriata, traditionally chosen by lot from the centuries of the first class and the twelve classes of equites, and thus highly influential. Certainly this is more plausible than Mommsen's perrogationem ('the successive asking for opinions': OLD s.v. perrogatio), which is not attested in any classical author.